Remarkable response of diffuse sclerosing osteomyelitis of the mandible to zoledronate by single infusion without prior treatment of other bisphosphonates. Issue 6 (November 2022) - Yamada, Manabu; Iwata, Sho; Nishi, Kentaro; Ochiai, Shunsuke; Araki, Daisuke; Soma, Tomoya; Yamada, Yuka; Miyashita, Hidetaka; Suga, Kenichiro; Asoda, Seiji
Abstract: Diffuse sclerosing osteomyelitis of the mandible (DSOM) is a nonsuppurative osteomyelitis mainly characterized by recurrent local mandibular swelling and pain. Because of the unknown pathophysiological mechanism underlying DSOM, treatment can be challenging. Reported treatment options include long-term analgesic medication, non-steroidal anti-inflammatory drugs (NSAIDs), antibiotics, corticosteroids, hyperbaric oxygen, and surgical treatment. However, these treatments cannot reliably lead to a long-lasting reduction of complaints. Recently, bisphosphonates has been reported effective in managing DSOM. We herein report a case of DSOM with a favorable response to a single infusion of zoledronate without prior treatment of other bisphosphonates. The patient was a 19-year-old woman who visited our hospital complaining of swelling and remarkable spontaneous pain in the right mandibular angle region. Under the diagnosis of osteomyelitis of the mandible, the clinical symptoms were improved by administering an antimicrobial agent and anti-inflammatory analgesic, but computed tomography (CT) showed exacerbation of bone resorption. A biopsy showed fibrosis between the bone tissue and trabeculae, a finding consistent with post-inflammatory changes. 99mTc scintigraphy showed an abnormal accumulation in the right mandibular ramus. Based on these results, she was diagnosed with DSOM. As a result of discussing with the physician in charge of internal medicine, it became the policy of the bisphosphonates and the intravenous administration of zoledronate 4 mg was enforced. Her bone sclerosis and bone resorption showed an improving trend on CT three months after the zoledronate administration, and there have been no symptoms or exacerbation of findings in three years since the administration.